2001
DOI: 10.1007/s003600000169
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the thermal sensitivity of cytochrome c oxidase on the respiration rate of Arctic charr red muscle mitochondria

Abstract: To assess if cytochrome c oxidase could determine the response of mitochondrial respiration to changes in environmental temperature in ectotherms, we performed KCN titration of the respiration rate and cytochrome c oxidase activity in mitochondria from Arctic charr (Salvelinusfontinalis) muscle at four different temperatures (1 degrees C, 6 degrees C, 12 degrees C, and 18 degrees C). Our data showed an excess of cytochrome c oxidase activity over the mitochondrial state 3 respiration rate. Mitochondrial oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 0 publications
8
45
0
Order By: Relevance
“…The activity of this enzyme varied little across temperatures, differing by at most 30% across a 14°C range of assay temperatures and generally peaking between 27 and 32°C (Figs 3, 9). Similar patterns have been observed in some fish, amphibian and reptile species (Godiksen and Jessen, 2001;Glanville and Seebacher, 2006;Niehaus et al, 2011), but not in others (Caldwell, 1969;Blier and Lemieux, 2001). Furthermore, there were clear differences in thermal optima between the 22°C T E group (T opt of 27°C) and the 32°C T E group (T opt of 32°C).…”
Section: Developmental Plasticity Of Enzyme Activities and Thermal Opsupporting
confidence: 82%
“…The activity of this enzyme varied little across temperatures, differing by at most 30% across a 14°C range of assay temperatures and generally peaking between 27 and 32°C (Figs 3, 9). Similar patterns have been observed in some fish, amphibian and reptile species (Godiksen and Jessen, 2001;Glanville and Seebacher, 2006;Niehaus et al, 2011), but not in others (Caldwell, 1969;Blier and Lemieux, 2001). Furthermore, there were clear differences in thermal optima between the 22°C T E group (T opt of 27°C) and the 32°C T E group (T opt of 32°C).…”
Section: Developmental Plasticity Of Enzyme Activities and Thermal Opsupporting
confidence: 82%
“…The decrease of coupling ratios with temperature was elicited by different thermal sensitivities of oxidative phosphorylation capacity (state III) and proton leakage capacity (state IV ol ) showing lower Arrhenius activation energies for state III than for state IV ol . Progressive uncoupling with rising temperature was also reported by Hardewig et al (1999) and by Po¨rtner et al(1999b) for Antarctic species, whereas studies carried out with temperate zone eurytherms showed coupling ratios to be stable and independent of temperature (Blier et al 2001, Fischer 2002 or fairly insensitive to temperature (van den Thillart and Modderkolk 1978, Moyes et al 1988, Blier and.…”
Section: Respiratory Properties Of Liver Mitochondriamentioning
confidence: 79%
“…This complex is thought to act as an electron sink and to limit the ETS capacity (Arnold, 2012), and it has been suggested that thermally induced changes in COX affect respiratory regulation mainly through an impact on the redox state of the ETS (Blier and Lemieux, 2001). However, this complex is usually found to have an excess capacity that is required for adequate functioning of mitochondria at the different temperatures encountered by the species, thus allowing the ETS to be mainly in an oxidized state and to ensure a sharp thermodynamic gradient in the ETS under most thermal conditions (Blier and Lemieux, 2001;Blier et al, 2013;Hilton et al, 2010). Surprisingly, we did not find such an excess as the values for COX were only slightly higher than those for CI+CII-OXPHOS.…”
Section: Discussionmentioning
confidence: 99%